1999
DOI: 10.1136/thx.54.11.1027
|View full text |Cite
|
Sign up to set email alerts
|

Particulate air pollution and the blood

Abstract: Background-Particulate air pollution has been associated with excess deaths from, and increases in hospital admissions for, cardiovascular disease among older people. A study was undertaken to determine whether this may be a consequence of alterations in the blood, secondary to pulmonary inflammation caused by the action of fine particles on alveolar cells, by repeatedly measuring haematological factors in older people and relating them to measurements of exposure to airborne particles. Methods-One hundred and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
261
11
7

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(298 citation statements)
references
References 23 publications
18
261
11
7
Order By: Relevance
“…Decreases in circulating red blood cell (RBC) count, hemoglobin concentration, and hematocrit have been correlated with particulate exposure in humans (Seaton et al 1999) and in dogs (Clarke et al 2000), raising the possibility that enhanced ischemia may also be attributed to a decrease in the oxygen-carrying capacity of the blood. In a hematologic study carried out on the same dogs in parallel with the current study, Savage et al (2002) found decreased RBC and platelet counts, hemoglobin concentration, and hematocrit after CAPs exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in circulating red blood cell (RBC) count, hemoglobin concentration, and hematocrit have been correlated with particulate exposure in humans (Seaton et al 1999) and in dogs (Clarke et al 2000), raising the possibility that enhanced ischemia may also be attributed to a decrease in the oxygen-carrying capacity of the blood. In a hematologic study carried out on the same dogs in parallel with the current study, Savage et al (2002) found decreased RBC and platelet counts, hemoglobin concentration, and hematocrit after CAPs exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biologic pathways through which air pollution might increase the risk of cardiovascular mortality require further study, some cardiorespiratory pathophysiologic effects of air pollution that could increase the risk of cardiovascular disease and mortality have been observed in humans (Stieb et al 2002). Measures of ambient air pollution have been associated with poor cardiac autonomic control in the elderly (Liao et al 1999), increased heart rate (Peters et al 1999a), increased systolic blood pressure (Peters et al 1999b), increased plasma fibrinogen (Pekkanen et al 2000), increased plasma viscosity (Peters et al 1997), and possible sequestration of red cells in the circulation (Seaton et al 1999). Our results are consistent with the expectation that persons with serious respiratory or cardiovascular diseases should be those who are most sensitive to the biologic effects of air pollution.…”
Section: Discussionmentioning
confidence: 99%
“…The few ongoing air pollution cohort studies developed a strong focus on respiratory health, whereas short-term air pollution studies indicate that the cardiovascular system may play an important pathophysiologic role (27)(28)(29)(30). Among some of the large cohorts, data that is already available may permit investigation of whether genetic, societal, behavioral, and environmental factors modify the susceptibility to long-term effects of outdoor air pollution, an area with clear need for intensified research (1-3).…”
Section: The Cohorts Already Existmentioning
confidence: 99%